2015
DOI: 10.1016/j.hrthm.2015.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein triggers play an important role in the initiation of atrial flutter: Initial results from the prospective randomized Atrial Fibrillation Ablation in Atrial Flutter (Triple A) trial

Abstract: Pulmonary vein triggers play an important role in AFL. PVI can prevent the recurrence of AFL, even without CTI ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Mesquita et al reported that prophylactic CTI did not improve the outcome based on the gender, associated comorbidities, type of AF, LA volume, body mass index, or type of navigation . Even some studies reported that isolation of triggers in the PVs can eliminate both arrhythmia . Therefore, the role of prophylactic CTI block ablation in terms of freedom from risk of AF recurrence remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Mesquita et al reported that prophylactic CTI did not improve the outcome based on the gender, associated comorbidities, type of AF, LA volume, body mass index, or type of navigation . Even some studies reported that isolation of triggers in the PVs can eliminate both arrhythmia . Therefore, the role of prophylactic CTI block ablation in terms of freedom from risk of AF recurrence remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Mohanty et al suggested that the concomitant CTI ablation with PVI does not provide any added advantage, and PVI alone may be sufficient for control of both AF and AFL [20]. Schneider et al also showed that PVI can prevent the recurrence of AFL, even without CTI ablation [21]. These results, combined with the present results, indicate that we should re-evaluate the efficacy of concomitant CTI linear ablation with the PVI procedure in patients with AF without a previous typical AFL episode.…”
Section: Discussionmentioning
confidence: 99%
“…RIP = rest in piece recurrence of AFL, even without CTI ablation. 7 Furthermore, other authors have proved that in some patients with coexistent AF and AFL, PVI alone may be sufficient to control both arrhythmias. 8,9 In lieu of no optimal ablation strategy for patients with nonparoxysmal AF besides PVI, we consider that posterior wall isolation and LAA electrical isolation may currently represent the only strategies that have compelling data, proving a significant benefit in achieving freedom from all-atrial arrhythmias.…”
Section: F I G U R Ementioning
confidence: 99%
“…They compared PVI versus CTI ablation. They suggested that PV triggers play an important role in AFL and that PVI can prevent the recurrence of AFL, even without CTI ablation . Furthermore, other authors have proved that in some patients with coexistent AF and AFL, PVI alone may be sufficient to control both arrhythmias .…”
mentioning
confidence: 99%